Lifestyle modification intervention among pregnant women with hypertension based on the self-determination theory using M-Health - Heidari, Negar; Rajati, Fatemeh; Heidari, Paria; Rajati, Mojgan (Frontiers in Public Health, 2025)
BackgroundDigital health technologies have the potential to empower patients and enhance the management of chronic diseases, such as hypertension, which often suffers from low awareness and control rates in developing countries. This study aims to investigate the effectiveness of a lifestyle intervention tailored for hypertensive pregnant women, employing strategies derived from self-determination theory through a mobile health program.MethodsThe study utilized an experimental pre-test/post-test design with a two-month follow-up period. It examined the impact of an educational intervention on pregnant women with hypertension in Kermanshah, Iran, from 2021 to 2023. Sixty pregnant women with hypertensive disorders were recruited from medical centers and randomly assigned to either the intervention group (N = 30) or the control group (N = 30). A mobile app was employed to deliver the educational intervention, addressing lifestyle factors such as nutrition, physical activity, and stress management. The app’s effectiveness was assessed based on multiple criteria, including content quality, data accuracy, decision support, language and cultural sensitivity, user feedback interpretation, and personalized recommendations.ResultsAfter the intervention, repeated measures ANOVA indicated that the intervention resulted in statistically significant improvements in all study variables within the intervention group compared to the control group (p < 0.05), with the exception of blood pressure (p > 0.05). These changes remained significant during the follow-up period, except for relatedness, moderate physical activity, sitting time, and total physical activity (p > 0.05). The intervention significantly enhanced both controlled autonomy (p < 0.001, η2 = 0.21) and autonomous autonomy (p < 0.001, η2 = 0.30), as well as competence (p < 0.001, η2 = 0.27). The effect on relatedness was marginally non-significant (p = 0.053, η2 = 0.053). Improvements in nutrition, physical activity, and perceived stress were significant across between-group, within-group, and interaction effects (p < 0.05). All levels of physical activity showed significant improvements (p < 0.05), except for low physical activity (p > 0.05). There were significant between-group differences in both systolic and diastolic blood pressure (p < 0.05), but no significant within-group or interaction effects were observed.ConclusionThe M-Health intervention led to improvements in lifestyle factors and self-determination constructs, with the exception of relatedness, which may be attributed to the limited features of the app. Although blood pressure did not change significantly, the reduction in systolic pressure could still be clinically meaningful. M-Health interventions grounded in self-determination theory show promise for supporting hypertensive pregnant women.